2-(y+2)=y

Simple and best practice solution for 2-(y+2)=y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-(y+2)=y equation:


Simplifying
2 + -1(y + 2) = y

Reorder the terms:
2 + -1(2 + y) = y
2 + (2 * -1 + y * -1) = y
2 + (-2 + -1y) = y

Combine like terms: 2 + -2 = 0
0 + -1y = y
-1y = y

Solving
-1y = y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
-1y + -1y = y + -1y

Combine like terms: -1y + -1y = -2y
-2y = y + -1y

Combine like terms: y + -1y = 0
-2y = 0

Divide each side by '-2'.
y = 0

Simplifying
y = 0

See similar equations:

| 46x^3+43x^2+5x= | | 2-(y+2)=ey | | 2x(x+3)=12 | | 3x-12+16=2x+10 | | X+5x=3 | | 5x+17-4x=9+4x-7 | | x+7m=78m^2 | | 346*65=x | | 4x+7x-3x=34+6 | | -10x+(-5)-x=28 | | -10x+5-x=28 | | 34*15=x | | -3y-3=1+2y | | -9x-4=203 | | X^2+94=-2 | | 3px(-4)=6 | | 5y-4=19y+108 | | 3x-12+8x=87 | | 0=3x(x-4)(x-1) | | -x+x+30= | | 0=3x(x-4)(x-1) | | 2x-48=52 | | 2x-48=52 | | x+Bx+25=(x+5) | | 2a+3b-5a= | | 6x-4=44-2x | | 2(x-6)-9=19-6x | | 10+.3x=x-2 | | 48-2x=8x+8 | | 10+1.3x=x-2 | | 42975-125m=45000-350m | | 0.3t+-0.3t=x |

Equations solver categories